Computer-Supported Collaborative Learning 2008
DOI: 10.4018/978-1-59904-753-9.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Diversity in Collaborative Virtual Teams

Abstract: Computer supported collaborative learning environments (CSCLEs) is one of the innovative technologies that support online education. Successful design and implementation of such environments demand thorough analysis of many parameters. This chapter studies the impact of diversity in learner-learner interactions in collaborative virtual teams through a social and cultural perspective. Social differences include gender, race, class, or age. Cultural differences refer to matters like how an individual’s cognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…This may be explained by women's preferences for collaborative learning (Belenky et al, 1997) and advantages in nonverbal expression and decoding skills (Hall, 1987), whereas male students are more goal-oriented and may still need more visual clues obtained in F2F discussion for better idea elaboration. Some similar results regarding the online social interactions can also be observed in other studies (McSporran & Young 2001;Michailidou & Economides, 2007). In addition, a relatively more recent study has reported that young females have higher Internet self-efficacy for online communication than young males (Tsai & Tsai, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…This may be explained by women's preferences for collaborative learning (Belenky et al, 1997) and advantages in nonverbal expression and decoding skills (Hall, 1987), whereas male students are more goal-oriented and may still need more visual clues obtained in F2F discussion for better idea elaboration. Some similar results regarding the online social interactions can also be observed in other studies (McSporran & Young 2001;Michailidou & Economides, 2007). In addition, a relatively more recent study has reported that young females have higher Internet self-efficacy for online communication than young males (Tsai & Tsai, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Triantafillou et al (2006) mentioned that language, and culture should be taken into account when designing adaptive educational interfaces to optimise learner's potential to benefit from the system's design in terms of knowledge acquisition. Michailidou and Economides (2007) argued that computer supported collaborative learning environments and instructors should take into consideration cultural factors that influence learners' learning. Pittman (2007) called for converging instructional technology and intercultural pedagogy in teacher education.…”
Section: Metj 24mentioning
confidence: 99%
“…Several researchers mentioned that collaboration may affect each participant's cultural characteristics (Chang and Lim, 2002;Cifuentes and Murphy, 2000;Ferdig et al, 2007;Holloway and Valentine, 2000;Lim and Zhong, 2005;Michailidou and Economides, 2007). Computer-based collaborative work can transform classroom cultures, the roles of teachers and the expectations of learners (DeVoogd, 1998).…”
Section: Collaboration May Affect Learner's Culturementioning
confidence: 99%
See 2 more Smart Citations